Tafilelt, the Neo Traditional Model of Ksour in Algeria: Assessment of the Multifunctionality of Urban Spaces - SOUIDI MANEL; BESTANDJI SIHAM (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
The new ksar of Tafilelt situated in Ghardaia in southern Algeria has attracted a lot of interest in scientific work, being a « neo-traditional » urban model that reproduces the principles of composition and spatial organization of the ksour in the pentapolis of Ghardaia. This ksar embodies the adaptation between tradition and modernity: it refers to the local setting of the ksourien space production, contributes to the valorization of these ancient centres that date back to the XIth century.In parallel to the work of thesis undertaken on « the neo-traditional models of reference in Algeria for the new cities », we ask the following questions according to the case of Tafilelt: Is this ksar really a model Does it take the traditional model fully Is this indeed a new city? In addition, speaking about the concept of multifunctionality. How to detect this integral reproduction in the urban spaces between the old and the new ksari. This work will be an analytical reading of the spaces of this ksar according to the four concepts above, namely: the urban model of reference, the criteria of the new city, the criteria of the former ksour and the multi-use character of their spaces. We will try to apply the concept of multifunctionality on urban spaces in different scales to assess the multifunctionality of the ksar’s spaces in a comparative approach between the old and the new ksour.